MODEL AND METHODS OF MANAGEMENT OF EFFICIENCY OF USE OF PRODUCTION AND TECHNOLOGICAL POTENTIAL OF ROLLING STOCK OF RAIL TRANSPORT (Transport systems and technologies, 2021)
The article considers the problems management of efficiency of use of production and technological potential of rolling stock of rail transport. It is investigated that to improve the efficiency of functioning requires a comprehensive solution of many problems, with the rational use of labor, material and labor resources. A set of many tasks aimed at improving and ensuring the level of efficiency of rail transport facilities and systems is considered. It is investigated that in order to achieve the required level of efficiency of rolling stock operation it is necessary to improve the management process by system model of the set of problems of efficiency of use of production and technological potential of work of rail transport.As a result of solving the problema mathematical model of the set of problems was proposed, which became the basis for building a system model of the set of problems. The decomposition method and AllFusion ProcessModeler software were used to build the system model. The paper considers the task of ensuring the required level of efficiency in the use of production and technological potential of rolling stock and the proposed ways to solve it. There is also a comprehensive review of objects, systems and processes, which involves their identification, providing a formalized description. On the basis of which a model and method of diagnosis were proposed, which inopen the possibility of interaction between the management of the subsystem of diagnostics and planning of work of objects and systems of rolling stock on the basis of the actual technical condition. The solution in this way will increase the indicators of the main aspects of production and technological potential, which is the purpose of this work.
Keywords: diagnostic method, model, decomposition, system analysis, system, production and technological potential.